O Estatuto da metáfora segundo Merleau-Ponty (Phenomenology, Humanities and Sciences, 2025)
In the chapter Interrogation and Intuition, published in “The Visible and the Invisible”, Merleau-Ponty says that language is a paradox because, on the one hand, it forbids coincidence, absolute sympathy with objects, since, if this language were possible, it would be mute, that is, reduced to silence; on the other hand, while it is true that there is no pure, adamic, diamond language, it is a fact that poets and writers discover, through metaphors, a language capable of speaking about the world. Within language, there is a role reserved for metaphor, which produces ironic meaning. This study aims to follow this paradox as Merleau-Ponty presents it to us in “The Visible and the Invisible” and in “Notes on Husserl's course The Origin of Geometry”. In this course, Merleau-Ponty insists on the concept of “difference” or “deviation of level” (fr. écart). The concept of deviation is fundamental to the articulation between the phenomenology of expression and the ontology of the sensible and represents a novelty present in Merleau-Ponty's courses at the Collège de France in the 1950s. Language must be understood from the point of view of the use of operative metaphors, in other words, from the deviation in level between spoken speech and speaking speech. The operation of metaphor is representative of the beginning of language and is founded on the field of the sensible. Merleau-Ponty criticizes the evidence of scientific statements and the ideas in the name of the opacity of the sensible that is revealed in the metaphorical operation. The conclusion of the article presents the relationship between metaphor and indirect language.
Keywords: Merleau-Ponty; Language; Metaphor